Long-run Trend and Determinants of Terms of Trade of Iran - Yousefvand, Saman; Najarzadeh, Reza; Heidari, Hasan; Agheli, Lotfali (International Journal of Economics and Financial Issues, 2017)
This paper examines the trend and determinants of terms of trade of Iran. Using a Vector-Error Correction model (VECM), two models has been estimated for Iran’s economy. Terms of trade in model I is the net barter terms of trade; and in model II is the ratio of export to import unit values. Annual data of 1966-2012 and seasonal data of 1991-2011 have been used for respectively, model I and II. Four variables have been identified as main explanatory elements of variation in terms of trade over time; these variables are output, exchange rate, trade openness and oil prices. VEC model is used to capture the long-run interaction among variables. In first part of the article, the trend in terms of trade is evaluated to investigate whether there is a negative trend exists among TOT data as the Prebisch- Singer Hypothesis suggests there would be such a tendency in a commodity exporting country like Iran. Results show that there is not a significant decreasing trend in TOT data. VECM results show short-run causality from all variables to the terms of trade in. Also variables converged to their equilibrium levels. The correlation of the terms of trade is negative with exchange rate and positive with output, oil prices and trade openness in long-run. Keywords: Terms of Trade, Unit Root Test, VECM model JEL Classifications: F11; C8; C32